1976
DOI: 10.1016/0010-0285(76)90017-7
|View full text |Cite
|
Sign up to set email alerts
|

Adult-child discourse: Developmental interaction between information processing and linguistic knowledge

Abstract: The discourse interaction between adult and child was examined in terms of the content of their utterances, and the linguistic and contextual relations between their messages, in order to investigate how children use the information from adults' input sentences to form contingent responses. The analyses described were based on longitudinal data from four children from approximately 21 to 3 6 months of age. Categories of child discourse, their development and their interactions with aspects of prior adult utter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
167
2
7

Year Published

1980
1980
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(186 citation statements)
references
References 18 publications
10
167
2
7
Order By: Relevance
“…Other studies have concluded that in pretending, children do not blindly mimic a model but demonstrate only those aspects that they can understand or assimilate (Gottlieb, 1973;Harnick, 1978;McCall, Parke & Kavanaugh, 1977;Scollon, 1976;Slobin & Welsh, 1973). In fact, the modeled actions seem to act as general facilitators of pretending (Watson & Fischer, 1977) as long as the modeling and pretending occur in a context in which the behaviors are appropriate for the child (see Bloom, Rocissano, & Hood, 1976). Also, a similar modeling procedure is commonly used in play therapy with preschool children: The therapist acts out or explains a story or theme of some kind, and the child frequently picks up the story or theme and incorporates it into his or her play (e.g., Harter, 1977).…”
mentioning
confidence: 99%
“…Other studies have concluded that in pretending, children do not blindly mimic a model but demonstrate only those aspects that they can understand or assimilate (Gottlieb, 1973;Harnick, 1978;McCall, Parke & Kavanaugh, 1977;Scollon, 1976;Slobin & Welsh, 1973). In fact, the modeled actions seem to act as general facilitators of pretending (Watson & Fischer, 1977) as long as the modeling and pretending occur in a context in which the behaviors are appropriate for the child (see Bloom, Rocissano, & Hood, 1976). Also, a similar modeling procedure is commonly used in play therapy with preschool children: The therapist acts out or explains a story or theme of some kind, and the child frequently picks up the story or theme and incorporates it into his or her play (e.g., Harter, 1977).…”
mentioning
confidence: 99%
“…With increasing experience, children develop expertise, which leads to increased levels of flexibility and generalization of knowledge. The result is more contextually appropriate behavior in increasingly novel conditions [Bloom et al, 1976;Ross, 1982;Rutter and Durkin, 1987;Eckerman and Didow, 1989]. Although these principles have not been systematically examined in intervention studies involving children with autism, they have implications for designing interventions where diversity and complexity of stimuli within learning contexts are systematically engineered, and tailored to the child's emerging and established abilities.…”
Section: Why Early Intervention For Autism?mentioning
confidence: 95%
“…For conversation to be sustainable for very long, each party's contribution must be relevant to the previous speaker's turn. With development, children increase the contingency of their conversational contributions (Bloom, Rocissano, & Hood, 1976).…”
Section: Communicative Developmentmentioning
confidence: 99%